Accurately accelerating drug design workflow - Alhossary, Amr Ali Mokhtar (2019)
In a world where pathogenic bacteria, viruses, as well as cancer develop resistance to drugs on faster pace than discovering new ones, researchers bear the heaviest weight to design new drugs to overcome such phenomenon of drug resistance. Drug design is one of the most challenging tasks in computational and structural biology, which aims at developing new drugs or enhancing currently known drugs against certain diseases based on the knowledge of a biological target.